A STUDY ON ECONOMICAL AND SOCIAL CONDITION OF INDIA DURING FIRST WORLD WAR - 1. Tuhin Poria , 2. Dr. Uma Dubey (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The war is effective in disrupting the social and economic standard of the nation. Therefore, the main purpose of this chapter of the thesis is to reflect the economic policies of British India. Apart from that, this is significant in reflecting the effect of the war in bringing changes in the economic policies. Hence, this chapter is to demonstrate the role played by the governor for managing several situations in India during the war time. British policies caused deep and significant changes in the structure and the development of the Indian economy. India was an industrialized nation before the advent of the British Empire and boasted of textile mills, handicraft industries and agricultural produce (Rai, 2022). The application of British economic policies brought about dramatic changes in the Indian economy. It mostly lays a negative impact on the indigenous factories for the benefit of Britain. Deindustrialization of the country is the result of British imperialism. Other than that, the British policies in the textile sector entailed free trade in British machine made goods and high import duties on Indian goods (Frederick and van Nederveen Meerkerk, 2023).